IMPLEMENTASI PERATURAN DAERAH TENTANG PELAYANAN PUBLIK DI KOTA SURABAYA - Windiani Windiani (Jurnal Sosial Humaniora, 2010)
This research aim to know about interpretation and implementation low of Public Service in Surabaya. Beside that, to aim for complicated researchs about region law within public service in Surabaya and give in put to decision maker to attitude law of public service in Surabaya. This research do in Surabaya city and take many public officials as informant with snowball sampling model. This is kualitatif research with use diskriptif analysis. Out put of this research show that interpretation of public officials to law of public serveice in Surabaya city is diferents because; First, the law of public service is new, so there is not technical references to interpretation law of public service. Second, every public service have subject service and character diferences so, interpretation of pubic service become different. Third, there is not the